PENYIDIKAN KASUS PELANGGARAN LALU LINTAS YANG MENYEBABKAN KEMATIAN: STUDI PADA SATLANTAS POLRESTA DELI SERDANG - M. Adityo Andri Cahyo Prabowo; Madiasa Ablisar; Sunarmi Sunarmi; Marlina Marlina (Universitas Dharmawangsa, 2023)
ABSTRACTThe process of handling traffic violation cases often experiences obstacles, especially in theinvestigation of traffic violation cases that cause fatalities. This study deliberately raises theObstacles faced by the Deli Serdang Police Traffic Unit in investigating and investigating casesof traffic violations that caused the death of motorized vehicle drivers, and the efforts of the DeliSerdang Police Traffic Unit in overcoming obstacles to investigations and investigations intocases of traffic violations that lead to the death of motorists. This research is a legal researchthat is descriptive in nature. Using a statutory approach. The results of the study show that:Obstacles faced by Sat Then investigators in investigating cases of violations that lead to death.The efforts made by the investigators are a process of raising awareness for Motorized Vehicledrivers to prioritize safety when driving on traffic roads that do not have road dividers. Wherethe driver's awareness and understanding efforts when overtaking the vehicle in front shouldtake into account the speed, space and time of the motorized vehicle being driven to avoidtraffic accidents; and the public should provide direct witness testimony in the field where thecrime scene (TKP) was conducted to the Traffic Unit Officer of the Deli Serdang Police who wason duty because to maintain the integrity of the information obtained from witnessing a trafficaccident as a whole.Keywords: Violation; death; Deli Serdang Traffic Unit